Al-Jawdah factors for blended learning evaluation in higher education / Mohd Norafizal Abd Aziz, Haslinda Noradzan and Nor Zalina Ismail - Abd Aziz, Mohd Norafizal; Noradzan, Haslinda; Ismail, Nor Zalina (2016)
The new way of learning implementation such as blended learning has emerging the new paradigm shifts to the learning practices. The mixed learning practices in blended learning adopting into formal and non-formal learning, has create issues to determine the quality of the blended learning implementation. From the current work observation, there is no adequate quality evaluation criterion that identified and adopted in the blended learning implementation. Therefore, this paper will propose the use of quality criteria known as Al-Jawdah factors which can be apply into blended learning implementation with four factors identified consists of learners, instructors, learning content and technology. Each factor will be discussed the appropriate quality aspects according to the critical success factors identified from the previous work. To enhance the use of the propose factors in real implementation of blended learning, we will discuss the planning to adopt the propose factors in a selected blended learning implementation in UiTM Pahang that will evaluate the effectiveness of blended learning. This will benefits UiTM Pahang to identify the further improvements need in blended learning implementation that will benefits the initiatives of blended learning implementation for UiTM Pahang and UiTM as well.